Advanced Real Time Imaging II Cutting-Edge Techniques in Materials Science Studies - Nakano, Jinichiro; Pistorius, P Chris; Tamerler, Candan; Yasuda, Hideyuki; Zhang, Zuotai; Dogan, Neslihan; Wang, Wanlin; Saito, Noritaka; Webler, Bryan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
"Real time" imaging techniques have assisted materials science studies especially for non-ambient environments. These techniques have never been collectively featured in a single venue. The book is an assembly of materials studies utilizing cutting edge real time imaging techniques, emphasizing the significance and impact of those techniques.
Real Time Imaging -- Cutting Edge Techniques -- Non-Ambient Conditions.
Keywords: Materials -- Analysis; Materials; Optical materials; Lasers; Spectrum analysis; Characterization and Analytical Technique; Materials Engineering; Optical Materials; Laser; Spectroscopy